Bacterial Patterns and Antimicrobial Susceptibility in Patients with Chronic Obstructive Pulmonary Disease Exacerbation - Hidayat, Hidayat; Megantoro, Gilang Kukuh; S, Retno Ariza; Nur, Muhammad (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2025)
Increased resistance of bacteriae that cause COPD exacerbations to several antibiotics commonly used in empirical therapy will reduce the effectiveness of therapy for COPD exacerbations. This will result in higher morbidity and mortality caused by COPD exacerbations. This study aims to determine the bacteriae and resistance pattern of bacteriae that cause COPD exacerbations in the Melati Room at RSUD. Dr. H. Abdul Moeloek Lampung for the period January to October 2022. This research was carried out at the Clinical Pathology Laboratory Installation of RSUD.Dr. H. Abdul Moeloek Lampung. The research method was retrospective descriptive, from 40 sputum culture test results from COPD patients were analyzed. The research results showed that the bacteria causing COPD exacerbations were Klebsiella pneumoniae (25%), Enterobacter spp (22.5%), Acinetobacter spp (17.5%), Pseudomonas spp (7.5%), Streptococcus spp (7.5%), Sphingomonas spp (5%), Escherichia coli (5%), Citrobacter koseri (2.5%), Staphylococcus epidermidis (2.5%), Enterococcus spp (2.5%) and Kocuria rosea (2.5%). Five samples were found with positive results for ESBL-producing bacteria (12,5%) and 17,5% were carbapenem resistant. It was concluded that the most bacteria were in the sputum of COPD exacerbation patients in the Melati Room at RSUD.Dr. H. Abdul Moeloek Lampung is Klebsiella pneumoniae (25%) with the highest resistance to Ampicillin (100%), and the highest level of sensitivity to Amikacin (100%) and Tigecycline (100%).